2013
DOI: 10.1177/1352458513501231
|View full text |Cite
|
Sign up to set email alerts
|

Observational case-control study of the prevalence of chronic cerebrospinal venous insufficiency in multiple sclerosis: results from the CoSMo study

Abstract: Background: Chronic cerebrospinal venous insufficiency (CCSVI) has been proposed as a possible cause of multiple sclerosis (MS). Objectives: The CoSMo study evaluated the association between CCSVI and MS. Methods: The primary end-point of this multicentric, case-control study was to compare the prevalence of CCSVI between patients with MS, patients with other neurodegenerative diseases (ONDs) and healthy controls (HCs). Color-coded duplex sonography was performed by a sonologist and the images were sent to one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
48
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 33 publications
6
48
0
Order By: Relevance
“…The most important limitation of the sonographic part of our study is the fact that Doppler sonography is an operator-dependent test [5,24,25]. It is also known that CCSVI is more likely to be diagnosed using ultrasound in a mildly dehydrated patient (for example, after fasting overnight) [26] and that diagnosis of CCSVI given with the use of Doppler sonography is poorly reproducible [24].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The most important limitation of the sonographic part of our study is the fact that Doppler sonography is an operator-dependent test [5,24,25]. It is also known that CCSVI is more likely to be diagnosed using ultrasound in a mildly dehydrated patient (for example, after fasting overnight) [26] and that diagnosis of CCSVI given with the use of Doppler sonography is poorly reproducible [24].…”
Section: Discussionmentioning
confidence: 98%
“…Such a unique vascular pathology is not often seen in the venous system, and for the time being no established non-invasive method for the assessment of such a condition exists [3]. Although in most of the published studies a diagnosis of CCSVI was given using Doppler sonography or MR venography, research on the validity of these tests was done primarily in the context of potential association of CCSVI with multiple sclerosis (MS) [1,[4][5][6][7]. However, it seems more accurate to validate a test against the established gold standard, and not against the presence or absence of the disease [8].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the prevalence of CCSVI highlighted in case-control studies has ranged from 0% to 100% in MS patients and from 0% to 36% in controls. 1,3,11,12,26,29,41 Noncontrolled studies have shown a higher prevalence. This fact sharply contrasts with the finding of significant intraluminal (septa, webs, membranes, fixed and rudimental valves, or wall stenosis) or valvular (tricuspid valves, enlarged and malposition valve leaflets, small accessory valve leaflets) abnormalities during post-mortem examinations or surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…This generated a considerable scientific controversy, mainly linked with the initially proposed Doppler ultrasound protocol apparently affected by low reproducibility [8,13].…”
Section: Introductionmentioning
confidence: 99%